TRADISI PRASEJARAH BERLANJUT PADA MASYARAKAT MEE DI KAWASAN DANAU TIGI , KABUPATEN DEIYAI - Amurwani Putri (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
This paper describes the prehistoric tradition continous at the Mee tribe. Where their live are still in the stage of simple, characterized by a prehistoric culture. Many forms of live and tradition of tribal communities Mee, both material culture (artifacts) as well as the behavior of those people that have relevance to aspects of prehistoric life. Research in this mountainous region find an overview of the use of stone axes as tools for farming, the use of shells as a means to pay andjewelry, the use of bone tool as a means for piercing and cutting, as well as the utilization of bark as materials for leather garmens and bags (noken). But it also will be discussed regarding the finding of cave and niches that formerly use as place of burial and worship, as well as overview of the ritual forms of agriculture (emomeni) and ritual pig feast (yuwo) in order to achieve social status (tonowi).